(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The aim of this study is to comparatively evaluate the fracture resistance of root canals obturated with 3 different obturating systems in endodontically treated teeth to find the effect of cold lateral condensation, Thermafil obturation and Downpack backfill obturation technique on the fracture resistance of endodontically treated teeth.60 freshly extracted single-rooted lower central incisor were divided based on type of obturation done into control groups (n = 12) where Group I (n = 12): Negative control group; teeth were neither instrumented nor obturated. Group II (n = 12): Positive group; only instrumentation, no obturation was performed and experimental groups (n = 12) where Group III (n = 12): Obturation using cold lateral compaction technique, Group IV (n = 12): Obturation using Thermafil obturation technique and Group V (n = 12): Obturation using Downpack backfill obturation technique. One way ANOVA and tukey’s multiple comparisons were applied to test for evaluation of fracture resistance among all the groups.The results showed that group I had the highest fracture resistance among all the groups followed by group IV, group V, group III and lowest was seen in group II. In conclusion, Group I had the highest fracture resistance among all the groups.